Archaeological University Education and Professional Archaeology in Sweden - Welinder, Stig (Current Swedish archaeology, 2021)
During the 19th century very few persons in Sweden recieved a doctoral degree in archaeology. Most of them found prestigious top-positions. Today there are about 100 persons with Ph. D.'s working in Swedish archaeology in positions from the top to the bottom of the professional hierarchy. Each year 150-200 students finish their basic education in archaeology. Most of them will never find a permanent full-time job as an archaeologist. The future of Swedish archaeology will very much depend on the ambitions of the general public, including tens of thousands of persons with a formal university education in archaeology but no job within the profession.